Comparative analysis of the fecal microbiota of healthy and injured common kestrel (Falco tinnunculus) from the Beijing Raptor Rescue Center - Guan, Yu; Bao, Lei; Zhou, Lei; Dai, Chang; Li, Zhisai; Zhang, Shuai; Shang, Yugang; Niu, Wenhui; Zhang, Yizhuo; Wang, Hongfang (PeerJ, 2023)
The gut microbiota is a complex ecosystem that interacts with many other factors to affect the health and disease states of the host. The common kestrel (Falco tinnunculus) is protected at the national level in China. However, the available sequencing data of the gut microbiota from the feces of wild common kestrels, especially for being rescued individuals by professional organization, remains limited. In the present study, we characterized the fecal bacterial communities of healthy and injured common kestrels, and compared the structure of their fecal microbiota by analyzing the V3–V4 region of the 16S rRNA gene using high-throughput sequencing technology with the Illumina MiSeq platform. We found that Firmicutes, Proteobacteria and Actinobacteria were the most predominant phyla in common kestrels. Further, the beta diversity analysis showed that changes in gut microbes were associated with injuries to the common kestrel. The Bacteroides/Firmicutes ratio was significantly lower in the injured group. At the genus level, Glutamicibacter showed significant difference in the two groups. The aim of our current study was to characterize the basic bacterial composition and community structure in the feces of healthy common kestrels, and then compare the differences in the fecal microbiota between healthy and injured individuals. Patescibacteria, Spirochaetes, and Glutamicibacter may be studied as potential biomarkers for certain diseases in raptors. The results could provide the basic data for additional research on the fecal microbiota of common kestrels and contribute to the rescue of wild raptors in the future.
Keywords: Common kestrel; Fecal microbiota; 16S rRNA gene; Wild raptor rescue